2019
DOI: 10.3390/ijerph16193750
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of a Menstrual Hygiene Management Intervention for People with Intellectual Impairments and Their Carers in Nepal

Abstract: Background: The Bishesta campaign is a menstrual hygiene management (MHM) intervention developed to meet the specific needs of people with intellectual impairments and their carers. It was designed and delivered in the Kavre district, Nepal. This paper explores the campaign’s feasibility and acceptability. Methods: The Bishesta campaign was delivered to ten people with an intellectual impairment and their eight carers. Data on the feasibility and acceptability of the intervention was collected through: Structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…More than half of participants in the present study reported intellectual impairment; previous research indicates that with support women with intellectual impairment(s) and/or high support needs can understand and accept their menstruation [2,23] however, this is best achieved via the provision of menstrual education in the years leading up to menarche allowing time for knowledge acquisition and practice [12], and if the teaching tools and approaches are adapted to meet participants specific learning needs [31]. Menstrual interventions in Bangladesh for young adolescent women with CP and their mothers need to address these considerations and the conflicting requirement of menarche as a pathway to knowledge, as well as be physically, financially and socially accessible and inclusive.…”
Section: Discussionmentioning
confidence: 82%
“…More than half of participants in the present study reported intellectual impairment; previous research indicates that with support women with intellectual impairment(s) and/or high support needs can understand and accept their menstruation [2,23] however, this is best achieved via the provision of menstrual education in the years leading up to menarche allowing time for knowledge acquisition and practice [12], and if the teaching tools and approaches are adapted to meet participants specific learning needs [31]. Menstrual interventions in Bangladesh for young adolescent women with CP and their mothers need to address these considerations and the conflicting requirement of menarche as a pathway to knowledge, as well as be physically, financially and socially accessible and inclusive.…”
Section: Discussionmentioning
confidence: 82%
“…This can negatively affect carer's wellbeing, which in turn could impact on the person they support (5). As a result of this research, we developed, delivered and evaluated the Bishesta campaign: a MHM behaviour change intervention for people with intellectual impairments and their carers in Nepal (33,52). It promotes communication between young people and carers about what menstruation is, and how to manage it hygienically and with dignity.…”
Section: Discussionmentioning
confidence: 99%
“…Among people with disabilities, a limited evidence base suggests that older people, people with more significant activity limitations and those with mobility or self-care limitations are most likely to face WASH barriers [ [1] , [2] , [3] , 8 , 9 ]. In addition, people who experience incontinence, and women and girls who menstruate (see Table 1 for definitions of key terms), may have further unmet requirements for water and adequate WASH facilities [10] , [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%